Fluticasone propionate 750 μg/day versus beclomethasone dipropionate 1500 μg/day: comparison of efficacy and adrenal function in paediatric asthma. Issue 8 (1st August 1998) - Fitzgerald, Dominic; Van Asperen, Peter; Mellis, Craig; Honner, Mareea; Smith, Lucia; Ambler, Geoffry
Abstract : BACKGROUND: Previous studies have suggested a 2:1 efficacy advantage of fluticasone propionate (FP) over beclomethasone dipropionate (BDP) in adults on high dose inhaled steroids and children on low dose inhaled steroids. The lower doses of FP required to provide equivalent efficacy to BDP also appear to have fewer systemic effects as measured by adrenal function. METHODS: The efficacy and safety of FP 750 μg/day and BDP 1500 μg/day were compared in 30 children with persistent asthma (requiring 1000–2000 μg/day of inhaled corticosteroids) in a 12 week randomised double blind crossover study. Medication was delivered by a spacer device in two divided doses. Primary efficacy variables were peak expiratory flows (PEF). Adrenal function was assessed by 24 hour urinary free cortisol levels at eight and 12 weeks and ACTH and low dose synacthen tests (LDST) at 12 weeks. The results were adjusted for sequence and period differences. RESULTS: There was no difference in the primary efficacy variables over the two 12 week treatment periods (difference in adjusted means for morning PEF 1.3 l/min (95% CI –6.1 to 8.8), p = 0.112) and symptom scores (cough, tachypnoea, wheeze, shortness of breath; difference in adjusted means of night time scores: –0.06 (95% CI –0.14 to 0.03); p = 0.136). Similar degrees of mild adrenal dysfunction were found during BDP and FP treatment phases. Identical height gain velocities were shown during the corresponding periods. CONCLUSIONS: FP 750 μg/day is as effective as BDP 1500 μg/day in children with persistent asthma. At these very high doses we were unable to demonstrate a safety advantage of FP over BDP as assessed by adrenal function. However, measures of adrenal function may have been influenced by concurrent and previous systemic steroid usage, and possibly by effects of disease activity.